Hospitality and tolerance as ways of seeing the encounter with the other. A Derridean reading - Balcarce, Gabriela (Estudios de Filosofía, 2014)
This article attempts to trace the historical genealogy of Derrida’s notion of ‘hospitality’ the end of inquiry. It is for this reason that, at the beginning of our work, we will brie y address some features of ancient hospitality from the Odyssey, and then move to an analysis of the concept of tolerance in modernity, through three of its greatest defenders: John Locke, Voltaire, and John Stuart Mill. With these ideas in mind we then try to sketch the problem of hospitality from a Derridean perspective and from the influence of Emmanuel Levinas’ philosophy, in order to emphasize the importance of ethical and political thought of the other as other.